A RETROSPECTIVE DOCUMENT REVIEW ON THE DISCHARGE OF ADOLESCENT PSYCHIATRIC PATIENTS IN A MALAYSIAN PSYCHIATRIC HOSPITAL - Muhammad Amin, Ahmad Zaki; Nurasikin, Mohamad Shariff; Azlina, Daud; Rekaya, Vincent Balang; Khamini, Tharumarajah (IIUM Press, 2025)
Adolescents in Malaysia face a range of serious mental health challenges that often lead to repeated admissions to psychiatric wards. To ensure continuity of care and the effectiveness of long-term treatment, proper discharge intervention and comprehensive interventions prior to discharge are essential. This study aims to explore the current discharge interventions provided to adolescent psychiatric patients in a psychiatric hospital located in northern Peninsular Malaysia. Using a descriptive qualitative design, discharge records of 81 adolescent psychiatric patients admitted between 2021 and 2023 were reviewed. A data abstraction checklist was developed to systematically extract relevant information from the documents. Content analysis was conducted using the READ (Read, Extract, Analyse, Distil) approach to identify key patterns and gaps. Preliminary findings indicate an absence of standardised discharge intervention protocols. Notably, four critical components were frequently missing from the discharge process: integration of technology, linkage to community resources, collaboration with schools, and access to peer support. These findings underscore the urgent need for a structured and standardised discharge framework tailored to adolescents with psychiatric conditions. Strengthening discharge interventions could help reduce hospital readmissions and support sustained recovery within the community. Future research should delve deeper into specific psychiatric issues, particularly among adolescents with a history of suicide, to inform targeted discharge strategies.